2007
DOI: 10.1097/gco.0b013e3280129b0f
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal surgery in advanced ovarian cancer

Abstract: By performing aggressive intestinal surgery such as combined bowel resection, optimal cytoreductive surgery can be performed in 70-98% of cases. The morbidity associated with intestinal surgery is acceptably low. Prognostic benefits for intestinal surgery are clear in patients with operable ovarian cancer with no residual disease. Women with suspected ovarian cancer should therefore be referred to centers with experienced tumor surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Since then, many studies have shown that aggressive cytoreduction increases survival when resulting in small or no gross residual disease. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] In an analysis of data from 6 major GOG trials, Winter et al 32 found that patients with any residual disease had an increased risk for death compared with those who had microscopic residual disease. In a study of 408 patients with stage IIIC ovarian cancer, Eisenkop et al 33 showed that cytoreducing tumors to no visible disease influenced survival more significantly than the extent of metastatic disease present before surgery.…”
Section: Evidence For Aggressive/ultraradical Cytoreductive Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, many studies have shown that aggressive cytoreduction increases survival when resulting in small or no gross residual disease. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] In an analysis of data from 6 major GOG trials, Winter et al 32 found that patients with any residual disease had an increased risk for death compared with those who had microscopic residual disease. In a study of 408 patients with stage IIIC ovarian cancer, Eisenkop et al 33 showed that cytoreducing tumors to no visible disease influenced survival more significantly than the extent of metastatic disease present before surgery.…”
Section: Evidence For Aggressive/ultraradical Cytoreductive Surgerymentioning
confidence: 99%
“…The tradeoff is increased morbidity. [18][19][20][21][22][23][24][25][26][27][28][29][30][31]44,54,55 Original Article Wakabayashi et al…”
Section: How Likely Is Optimal Cytoreduction?mentioning
confidence: 99%
“…Besides being a part of debulking surgery, intestinal surgery may be also needed for iatrogenic bowel injury or intestinal obstruction. In addition, bowel resection is often required for abdominal and pelvic recurrences and in palliation of intestinal obstruction (8).…”
Section: Introductionmentioning
confidence: 99%